2007
DOI: 10.1152/ajpheart.00413.2007
|View full text |Cite
|
Sign up to set email alerts
|

Aging enhances pressure-induced arterial superoxide formation

Abstract: The purpose of this study was to investigate the mechanisms that regulate superoxide (O(2)(*-)) production as a function of an acute elevation of intravascular pressure and age. Mesenteric arteries isolated from young (6 mo) and aged (24 mo) male Fischer 344 rats were used. O(2)(*-) production in vessels in response to 80 (normal pressure, NP) and 180 (high pressure, HP) mmHg was determined by the superoxide dismutase-inhibitable nitroblue tetrazolium (NBT) reduction assay. In vessels exposed to NP, O(2)(*-) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…11,12,27 Experimental elevation in blood pressure can directly lead to capillary rarefaction, most likely through an effect of increased generation of endothelial-derived reactive oxygen species on microvascular integrity. 28,29 Capillary rarefaction can also antedate the onset of hypertension because reduced capillary density is observed in normotensive individuals at high risk of developing hypertension. 12 However, capillary rarefaction is not a generalized observation in those predisposed to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,27 Experimental elevation in blood pressure can directly lead to capillary rarefaction, most likely through an effect of increased generation of endothelial-derived reactive oxygen species on microvascular integrity. 28,29 Capillary rarefaction can also antedate the onset of hypertension because reduced capillary density is observed in normotensive individuals at high risk of developing hypertension. 12 However, capillary rarefaction is not a generalized observation in those predisposed to hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory data exist on age-related changes on eNOS expression and NO production such that some show downregulation (5,14,52,58), while others suggest upregulation (22,60). Furthermore, increased production of reactive oxygen species were also reported during aging (14,24,27,48,60). Enhanced production of vasoconstricting factors also contributes to age-related endothelial dysfunction (5,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al showed the age-related increase in mitochondrial superoxide production in the testosteroneproducing cells of Brown Norway rat testes [55]. Superoxide production by xanthine oxidase and NO synthase in mesenteric arteries from aged rats was higher than in young ones [56].…”
Section: Aging and Senescencementioning
confidence: 99%